The role of the supreme courts at the national and international level : reports for the Thessaloniki International Colloquium, faculty of law of the Aristotle University of Thessaloniki, 21-25 May 1997 - Γέσιου-Φαλτσή, Πελαγία (Σάκκουλας Αντ. Ν., 1998)
This edition includes reports on the Thessaloniki International Colloquium (21-25 May 1997), covering all regional law systems worldwide. Here are examined the purposes, the actual achievements and the current functionality of Supreme Courts, not only in the context of existing legal families, but at an international and supranational level as well. These are examined in a comparative synthesis in the general report; and in more detailed presentations in the historical regional and international monographs.